Ethnobotanical applications of medicinal plants in the alpine flora of Marukh and Asogaha Nallah, Haramosh Valley, District Gilgit, Pakistan - Hasnain Abbas; Ali, Heera; Khan, Sher Wali; Khadim, Salim (Ethnobotany Research and Applications, 2024)
Background: This study, conducted from 2022 to 2024, explores the floristic diversity and ethno-medicinal significance of Haramosh Valley in the Karakoram Range. The region, renowned for its rich landscapes and traditional knowledge, confronts threats like deforestation. The primary objective is to document and conserve unique plant species and indigenous medicinal practices. Method: Field studies encompassed plant specimen collection, herbarium mounting, and identification. Ethno-botanical data was obtained through interviews with 130 locals, including herbalists, housewives, and elders, using semi-structured questionnaires. Statistical indices such as Relative Frequency Citation (RFC), Use Value (UV), Fidelity Level (FL), and Informant Consensus Factor (ICF) were employed for data analysis. Scientific databases provided additional information. Results: The results revealed that (65) alpine medicinal plant species in the Haramosh Valley were used to treat different illnesses. These species were organized into (51) genera and (32) families. The Asteraceae family became the most common, with (12) species and (9) genera. These plants were utilized as folk medicine in the study area and fell into the habit group. Perennial herbs are dominated by (42) species, followed by shrubs with (13) species, annual herbs with (5) species, and biennial herbs and trees with a single species each. The study offered some fascinating conclusions from the use of two quantitative data sets, UV and RFC, to investigate ethnomedical usage. Among the plant species examined, the ones with the highest RFC at (0.92) were Pleurospermum candollei, Swertia cordata, Bergenia stracheyi, Mentha arvensis, Primula denticulata, and Primula macrophylla, all of which had a (100%) FL, indicating their importance and frequency in the area. Conclusion: This study enhances our understanding of the intricate relationship between the people of the Haramosh Valley and plant biodiversity. It emphasizes the ecological significance of the area and advocates for conservation efforts amid increasing environmental threats. Documented ethno-medicinal knowledge provides insights into local communities' traditional healing practices, underscoring the urgency of preserving both the ecological and cultural heritage of Haramosh Valley. Sustainable practices are crucial for the well-being of the local population and the unique biodiversity of the region. Keywords: Ethno-botanical Significance, Medicinal Plant Species, Fidelity Level (FL), Informant Consensus Factor (IFC)